Peer learning in international higher education: the experience of international students in an Irish university. Issue 1 (2nd January 2019) - Idris, Aida; Ion, Georgeta; Seery, Aidan
Abstract : Some of the main concerns in international higher education are the feeling of isolation among international students and their inability to adapt to the host environment, which may result in sub-optimal academic performance. Theoretically, peer learning can be an effective method to reduce these problems since it has the capacity to address isolation and adaptability issues among international students in a way that improves their learning experience and outcomes. Given the above, our study was designed to investigate this topic, focusing on the experience of international students. In this exploratory case study of a leading Irish university, we adopted a survey method via questionnaire to quantify and compare the experiences of a sample of international students at the said university. Five aspects of peer learning were explored, namely usage rate, current practices, outcomes, challenges, and coping strategies. We also included an open-ended section in the survey instrument for respondents to offer qualitative suggestions to the host institution. Through methodological triangulation of the quantitative and qualitative data, we discovered diverse practices, challenges, and outcomes of peer learning across different groups of international students in this university. The paper concludes with a discussion of research implications and suggestions for future studies.